A spatiotemporal analysis of non-medical exemptions from vaccination: California schools before and after SB277. (November 2016) - Delamater, Paul L.; Leslie, Timothy F.; Yang, Y. Tony
Abstract: Childhood vaccination programs are considered one of the most beneficial public health programs in modern history. In the United States, the increasing use of non-medical exemptions (NMEs) from school entry vaccination requirements has garnered attention and scrutiny in the popular press, academic literature, and policy forums. In 2016, California law SB277 goes into effect, eliminating the NME option for students attending the state's public and private schools. Whereas SB277 is a strong move to increase vaccination coverage within California's schools, the new law contains an important caveat – students already having a valid NME (obtained prior to the 2016 school year) are "grandfathered" in until their next grade checkpoint (seventh grade). Although no new students will enter the California school system with a NME after 2016, the law's grandfather clause will allow NMEs to persist within the state school system until 2022. This analysis demonstrates how the past "build up" of students with pre-SB277 NMEs and the law's grandfather clause will act in combination to affect NME rates across the state after the implementation of SB277. We construct spatially explicit, yearly models of all students (K-12) enrolled in the California school system from 2011 to 2022. Our analysis finds that, although all regions of the state will eventually reach an NME rate of 0% by 2022, SB277's effect will be highly spatially and temporally variable. Some school districts will continue to experience elevated NME rates and increased risk of disease outbreak for years after SB277 is implemented. Our analysis highlights the potential spatially variant consequences of SB277's grandfather clause, providing important information for other states considering similar policy initiatives. Highlights: SB277's grandfather clause will delay the full effect of the law until 2022. NME rates are highly variable across CA school districts before and after SB277. Some regions remain at risk of disease outbreak well after SB277 is implemented. Future monitoring of medical exemptions as an alternative to NMEs is crucial.